PERSEPSI SISWA TERHADAP EFEKTIVITAS SANKSI DAN DENDA DALAM MENINGKATKAN DISIPLIN BELAJAR SISWA DI MTs.MIFTAHUL JANNAH PERANAP KABUPATEN INDRAGIRI HULU - ', Pebtriani; ', Hambali; ', Zahirman (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract This study was based on the rules in MTs.Miftahul Jannah Peranap the use of penalty sanctions and fines to improving student learning discipline, But usually fined in Indonesia one that is still lacking and not commonly used. so the author title”Student’s perceptions of the effectiveness of sanctions and fines to improving student learning discipline in MTs . Miftahul Jannah Peranap, sub district Indragiri Hulu.’’ formulation of the problem is how student’s perceptions of the effectiveness of sanctions and fines to improving student learning discipline in MTs. Miftahul Jannah Peranap. The purpose of this study is to know student’s perceptions of the effectiveness of sanctions and finesto improving student learning discipline in MTs. Miftahul Jannah Peranap. The population of this research are 258 people with a total sample of 65 people Instrument of data collection that questionnaire consists of 35 questions. Data were analyzed with qualitative descriptiveby percentage. From the calculation of the percentage of respondent sob tained answers Highly Effectiveas much as (78,1%) which lies in the range 76% - 100%. Thus the hypothesis that students' perceptions about the effectiveness of sanctions and fines is applied in MTs Miftahul Jannah Peranap “less effective” to improving student learning discipline. Based on research results, It can be concluded that the students' perception of the effectiveness of sanctions and fines to improving discipline for students at MTs . Mifathul Jannah Peranap Indragiri Hulu sub district is Very Effective.Keywords : Perception , Effectiveness , Sanctions and fines , Discipline Learning .